Elaborate the Concept of Snayu from Shushrut Samhita (AYUSHDHARA, 2022)
In the subject of Rachana sharir, The structures of the human body are studied with the help of morphology. Actions are formed on the basis of structures formed by Saptdhatu. Body composition is shaped according to the required physiology. The concepts in the Sushrut Samhita, which are superior in physical knowledge, are more scientific than those of other Samhita texts, because those structures were described by actual corpse research. Therefore, if you want to determine the suspicious structures in the body, the Sushrut Samhita is the standard for that. The Snayu is very important structure of the body. It is mentioned in the Samhita in various contexts. Snayu is mention in reference of Marma, Agnikarma, Shastra karma, Bandh Karma, Sivan Karma, Siravedha and Vatvikara. In this review article the Snayu structure is confirm as per the references in shushrut Samhita. Co-relation with modern anatomical structure has been done. This confirmation will help the physician to treat the Snayu vikruti as per the Chikitsa sutra stated in Shushrut Samhita.